PERAN EXPERIENTIAL VALUE DALAM MEMEDIASI PENGARUH EXPERIENTIAL MARKETING TERHADAP REPURCHASE INTENTION - Astari, Wayan Febri; Pramudana, Komang Agus Satria (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 10 Nomor 1 Tahun 2016, 2016)
The objective of this research is to analyze experiential value role in mediating the effect of experiential marketing on repurchase intention, through comprehensive review of previous studies and survey at the Gusto Gelato and Cafe. This study uses a quantitative approach in form of associative. The sample used were 185 respondents which was collected by purposive sampling method. Data were collected through questionnaire and interview. The analysis technique used to test the hypothesis is Structural Equation Modeling (SEM) with AMOS 16.00 software. The results of this study indicates that the experiential marketing has a positive and significant effects on experiential value and repurchase intention. In addition, the study also found that experiential marketing has a significant influence towards repurchase intention with experiential value as mediating variable.
Keywords: experiential marketing, experiential value, repurchase intention